Vaccination in Pregnancy against Pertussis: A Consensus Statement on Behalf of the Global Pertussis Initiative - Bahaa Abu-Raya; Kevin Forsyth; Scott A. Halperin; Kirsten Maertens; Christine E. Jones; Ulrich Heininger; Daniela Hozbor; Carl Heinz Wirsing von König; Amar J. Chitkara; Rudzani Muloiwa; Tina Q. Tan (Vaccines, 2022)
Infants are at high risk for severe morbidity and mortality from pertussis disease during early infancy. Vaccination against pertussis in pregnancy has emerged as the ideal strategy to protect infants during these early, vulnerable, first months of life. On 30 November and 1 December 2021, the Global Pertussis Initiative held a meeting that aimed to discuss and review the most up-to-date scientific literature supporting vaccination against pertussis in pregnancy and outstanding scientific questions. Herein, we review the current and historically published literature and summarize the findings as consensus statements on vaccination against pertussis in pregnancy on behalf of the Global Pertussis Initiative.